Implementasi Penilaian Kinerja Dalam Pembelajaran Matematika Berbasis Lesson Study di MTS Muhammadiyah Grogol (Pada Siswa Kelas VII Semester Gasal Tahun Ajaran 2016/2017) - Firdhaus, Nurul; , Dr. Sumardi,M.Si (2017)
This research aimed to (1) To determine the understanding of math teachers in MTs Muhammadiyah Grogol about performance assessment, (2) To determine extent of math teachers in MTS muhammadiyah Grogol can make the instrument performance assessment, (3) Knowing the impact of the implementation of performance assessment model on learning outcomes and student activity in the learning of mathematics-based lesson study in MTs Muhammadiyah Grogol. This research is a qualitative descriptive. Subjects of this study are students of class VII A in MTs Muhammadiyah Grogol. The technique of collecting data using interviews, observation and documentation. Data analysis technique performed by three stages of data reduction, data presentation, and conclusion. It can be concluded that (1) Mathematic teachers in MTs Muhammadiyah Grogol not understand performance assessment models. (2) Teachers are never make an assessment instrument performance, teachers never to draw up an assessment rubric of performance and in making about teacher just took a collection of questions from LKS, (3) Implementation of performance assessment based lesson study in MTs Muhammadiyah Grogol in Class VII A three stages, namely plan, do, and see. The performance assessment carried out in stages do can improve learning outcome, to motivate students to be more active, increase student interaction with students, students with teachers, also improving performance and quality of teachers.